Balances and Tensions in two Decades of University Accreditation in Argentina: Contributions for a Conceptual Model - Marquina, Mónica (2017)
This article aims to analyze the twenty years of experience in accreditation of university programs in Argentina from the perspective of the parties involved: evaluators, evaluated, technicians and decision-makers in the accreditation processes. It is assumed that the implementation of policy evaluation and accreditation in Argentina was not a linear, gradual, and simple process. Tensions and contradictions in the actions of the various actors involved are present in each of the areas where parties operate, within a main tension: evaluation for state control or evaluation as construction of meanings for improvement. Therefore, this study aims to study all the processes and their complexity in the context and characteristics of the university system of evaluation in Argentina, focused on the brief history of the estate evaluation agency: CONEAU. The results come from the analysis of information from documentary sources, interviews, and a representative evaluator´s survey. The conclusions propose a conceptual model in which attempts to graph “the evaluative arena”, with tensions and dynamics of these complex processes. The study is done from a perspective of the evaluation as political, participatory and sense - construction processes.